Research on University Data Governance Scheme Based on Data Platform - Xu, Minfu; Zhuang, Zhixiang; Wu, Junjun (International Journal of Computer Science and Information Technology, 2024)
A data governance solution for universities based on a data center is proposed to address various data management issues encountered in the construction of smart campuses. The solution consists of three parts: a data base, a data resource system, and a data center. With data assetization as the core and data serviceization as the goal, a complete set of mechanisms including data collection, standardization, cleaning and conversion, supporting management, and interface openness are adopted to cover the full lifecycle management of data, explore the value behind data, achieve synchronous improvement of data quality and data service quality, and promote the development of information technology and smart campus construction in universities.